Mapping Business Strategy of Electric Motorcycle Conversion Through Swot Analysis and Business Model Canvas - Febriza Imansuri; Fredy Sumasto; Mohammad Wirandi; Siti Aisyah; Al Kautsar Permana; Safril (Jurnal Ilmiah Dinamika Rekayasa, 2024)
Converted electric motorcycles are the outcome of transforming motorcycles that run on fossil fuels into electric ones. This conversion aims to promote the growing adoption of electric vehicles, prolong the lifespan of motor vehicle products, and mitigate carbon emissions in the transportation sector. Hence, the objective of this study is to ascertain and evaluate the market position of the converted electric motorcycle industry by utilizing Strengths, Weaknesses, Opportunities, Threats (SWOT), and Business Model Canvas (BMC) analysis. Primary data collection involved conducting interviews and utilizing brainstorming approaches with professionals from electric vehicle manufacturers and academia. Nine business strategy models for converted electric motorcycles were derived from the investigation using the BMC technique. According to the examination of the Internal Factor examination Summary (IFAS) and External Factor Analysis Summary (EFAS) matrices, a growth strategy has been selected. This approach indicates that the business possesses strengths and opportunities. Therefore, it requires policies that promote rapid expansion through comprehensive, integrated, and diversified methods. Recommendations for further research include exploring company strategies that use a circular and sustainable approach.